PRO-EUROPEAN VALUES OF HIGHER EDUCATION STUDENTS: THE EXPERIENCE OF IMPLEMENTING J. MONNET MODULE - Goncharova, Olgа; Maslova, Alina (Studies in Comparative Education, 2025)
The article deals with the main features and principles of forming value orientations of higher education students. It emphasizes the role of higher educational institutions in fostering the conditions for the promotion of universal and European values. Based on the analysis of the research works on European integration in terms of education the authors have made a conclusion that higher education in Ukraine is characterized by systemic changes through reforms aimed at creating a system for ensuring and continuously improving the quality of higher education that aligns with the recommendations and standards of the European Higher Education Area. The aim of this paper is to share the experience of Bogdan Khmelnitsky Melitopol State Pedagogical University in strengthening the EU common values in the education and training of future foreign language teachers under the framework of Jean Monnet Module of the ERASMUS+ programme. The authors describe in detail the Module’s objectives and outcomes; emphasize the impact of the Module on the development of future foreign language teachers’ competences in promoting the EU common values; present a list of key activities delivered within the Module framework; show how dissemination process is taking place.